2009
DOI: 10.3749/canmin.47.5.1117
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Geochemistry of Kimberlites Nk-2 and Kk-6, Narayanpet Kimberlite Field, Eastern Dharwar Craton, Southern India: Evidence for a Transitional Kimberlite Signature

Abstract: We have carried out a mineralogical and geochemical study on two previously uncharacterized kimberlites of coherent facies, NK-2 and KK-6, from the Narayanpet kimberlite field (NKF), Eastern Dharwar craton (EDC), southern India. Both these kimberlites have a distinct inequigranular texture resulting from two generations of variously sized olivine macrocrysts and groundmass microphenocrysts. Other groundmass phases include clinopyroxene (diopside), serpentine, phlogopite, calcite, spinel, perovskite and apatite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
5
2
Order By: Relevance
“…Olivine: Microphenocrystal olivine grains show a range in composition (Table 1) in Fo 83-91 and NiO (0.15-0.41 wt%), and NiO varies with Fo content (Figure 3). The composition of the olivine of this study is indistinguishable from data ( Figure 3) reported for other NKF pipes with Fo 86-92 and 0.10-0.40 wt% NiO; Chalapathi Rao et al, 2004;Chalapathi Rao and Dongre, 2009), Wajrakarur kimberlites (Fo 83-93 and 0.9-0.42 wt% NiO; Chalapathi Rao et al, 2004;Chalapathi Rao and Srivastava, 2009), Behradih orangeite, Bastar Craton (Fo 84-91 and 0.23-0.38 wt% NiO; Chalapathi Rao et al, 2011) and world-wide kimberlites (Fo 81.7 to 91.5 and up to 0.42 wt% NiO; Arndt et al, 2010). BSE imaging reveals little compositional variation (zoning) in olivine of this study ( Figure 2I).…”
Section: Mineral Chemistrycontrasting
confidence: 57%
See 3 more Smart Citations
“…Olivine: Microphenocrystal olivine grains show a range in composition (Table 1) in Fo 83-91 and NiO (0.15-0.41 wt%), and NiO varies with Fo content (Figure 3). The composition of the olivine of this study is indistinguishable from data ( Figure 3) reported for other NKF pipes with Fo 86-92 and 0.10-0.40 wt% NiO; Chalapathi Rao et al, 2004;Chalapathi Rao and Dongre, 2009), Wajrakarur kimberlites (Fo 83-93 and 0.9-0.42 wt% NiO; Chalapathi Rao et al, 2004;Chalapathi Rao and Srivastava, 2009), Behradih orangeite, Bastar Craton (Fo 84-91 and 0.23-0.38 wt% NiO; Chalapathi Rao et al, 2011) and world-wide kimberlites (Fo 81.7 to 91.5 and up to 0.42 wt% NiO; Arndt et al, 2010). BSE imaging reveals little compositional variation (zoning) in olivine of this study ( Figure 2I).…”
Section: Mineral Chemistrycontrasting
confidence: 57%
“…Clinopyroxene: Clinopyroxene occurs only as diopside and displays a tight chemical range (Table 3). The composition of diopside from kimberlites of this study is indistinguishable in Mg-Fe-Ca space from that previously reported from other NKF (Chalapathi Rao et al, 2004;Chalapathi Rao and Dongre, 2009) and WKF (Chalapathi Rao et al, 2004) pipes ( Figure 4A). However, their Ti (atomic) and Al (atomic) contents ( Figure 4B) have a restricted composition compared to that in other NKF pipes Behradih orangeite (Chalapathi Rao et al, 2011) and Krishna lamproites (at the NE margin of the Cuddapah Basin, Eastern Dharwar Craton; Chalapathi Rao et al, 2010a).…”
Section: Mineral Chemistrycontrasting
confidence: 52%
See 2 more Smart Citations
“…The depth (160-220 km) of this feature also coincides with the diamond stability field. Clearly such subducted material, if metasomatized, could provide a source for lamproitic magmatism, and it is important to note that several geochemical studies of eastern Indian para-kimberlites and lamproites have suggested a role for subducted components in their genesis, together with formation in the subcontinental lithospheric mantle, rather than convecting asthenospheric mantle (Chalapathi Rao and Dongre 2009;Chalapathi Rao et al 2010).…”
Section: Geodynamic Considerationsmentioning
confidence: 99%